Coexistência e conflitos humano-fauna: percepções da comunidade do Parque Estadual do Jaraguá (SP, São Paulo) - Thomaz, Clarice (Universidade Federal de São Carlos, 2024)
Human-wildlife relations can be characterized as interactions that can generate positive or negative impacts on wildlife, people, or both. When positive impacts reach both sides of the interaction, cohabitation is established. However, given the complex reality of human relations with wildlife, coexistence is not always achievable. When negative impacts affect both, human-wildlife conflict arises. These conflicts can be managed by seeking to improve the relationship between people and animals, significantly reducing negative impacts, and striving to establish coexistence. In this sense, environmental education can make important contributions by fostering an alignment between concepts, values, and forms of participation on the subject. This investigation aimed to understand elements indicating the community's perspective (staff and visitors) regarding conflicts and coexistence in Jaraguá State Park. To achieve this, we used data from semi-structured interviews, a mixed questionnaire, and Walking Ethnography. We also analyzed conflicts in the region based on wildlife incidents data provided by an institution that assists wildlife in the municipality. The results reveal conflicts primarily related to feeding animals in the Park and the presence of domestic animals in the area. Several actions, mainly educational, were identified as contributing to conflict management toward coexistence. Wildlife incident data align with the community's perception, indicating primates as one of the groups most involved in incidents, especially marmosets and capuchin monkeys. We understand the need for this management to be collaborative and dialogical, considering the participation of the entire community. At the end of the process and based on our results, we aimed to indicate preferred formats and themes for future production of educational materials contextualized to the area.
Coexistence and human-wildlife conflicts: perceptions of Jaraguá State Park community (SP, São Paulo)
Keywords: Coexistência humano-fauna; Conflito humano-fauna; Conservação da biodiversidade; Human-wildlife coexistence; Human-wildlife conflict; Biodiversity conservation; CIENCIAS BIOLOGICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::CONSERVACAO DE AREAS SILVESTRES; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO